Souls for Sale: an Introduction to the Motif of Bargaining with the Dark Side - Todorovska, Marija (Филозофско друштво на Македонија & ЗКФМ Антика, 2018)
The concept of a pact with some representative of the dark side persists in numerous cultural narratives and it almost always includes the steps of assumption of a soul, the possibility to trade it, and the risk/benefit ratio of doing so, a constant being the longing to gain superhuman abilities and/or skills and successes. The motif of the soul-selling to dark, evil beings in terms of exchange of submission and servitude for earthly advantages and superhuman abilities and the promise of happiness in this life or the next is briefly examined, through some understandings of evil in the world (various instances of evil demons, devilish adversaries, Satan); along the need for exculpation for wrong-doing and the implications of free decision- making; via the perception of the denouncement of the mainstream belief-systems and the contract with the Devil; and by pointing out some pact-with-the-Devil foundation stories.
Keywords: pact, devil, soul, Satan